Hormonal State rather than Age Influences Cut-off Values of Protein S: Reevaluation of the Thrombotic Risk Associated with Protein S Deficiency - Liberti, G.; Bertina, R. M.; Rosendaal, F. R. (Thrombosis and Haemostasis, 1999)
Of the well known risk factors for thrombosis protein S deficiency is one of the most difficult to diagnose with certainty. Reliable estimates for the prevalence of protein S deficiency in the general population are not available and the risk of thrombosis is a controversial issue. It has been shown that levels of protein S fluctuate over time. However the determinants of low levels of protein S in the healthy population are not clear. Therefore, we evaluated the influence of sex, age and hormonal state on the antigen levels of protein S in 474 healthy control subjects of the Leiden Thrombophilia Study (LETS). In univariate analysis, sex, age, oral contraceptive (OC) use and post-menopausal state all influenced protein S antigen levels. In a multivariate model for the whole sample only menopausal state and OC use had still an effect on the levels of total protein S and only menopausal state had an independent effect on the values of free protein S. On the basis of this analysis we established different cut-off levels for these subgroups and we re-evaluated in the Leiden Thrombophilia Study the risk of thrombosis for individuals with low protein S using these different reference ranges. With these specific cut-off points, we did not observe an increase in the risk of thrombosis in patients deficient of total protein S (OR 1.2, 95% CI 0.5-2.9) or free protein S (OR 1.3, 95% CI 0.5-3.5). When men and women were analyzed separately, the risk in women was 1.5 (95% CI 0.4-5.4) and 2.4 (95% CI 0.6-9.2) for total and free protein S deficiencies, respectively; and there was no increase in thrombotic risk for men. We conclude that it may be helpful to apply separate cut-off levels in the assessment of protein S levels. This does not, however explain the differences between our results and those of others in the estimate of thrombotic risk of protein S deficiency.